A Comparative Study of Digital Crypto Investor Protection Between Indonesian Law and Japanese Law - Alfarel Endito Putra; Aurora Jillena Meliala (Jurnal Ilmiah Dunia Hukum, 2025)
The development of blockchain-based financial technology has created a trading tool known as crypto assets. The rapid growth of crypto assets in Indonesia and Japan offers financial innovation but also presents high risks, including speculation, fraud, and inadequate investor protection. This study aims to analyze and compare the forms of legal protection for crypto asset investors in Indonesia and Japan, as well as assess the role of the government and exchange companies in ensuring the security and public trust in digital assets. This study uses a normative juridical method with a comparative approach, through an analysis of laws and regulations, government policies, and case studies of Indodax (Indonesia) and Coinchek (Japan). The results of this study indicate that the Indonesian legal system, currently regulated by Commodity Futures Trading Regulatory Agency (Bappebti ) still treats crypto as a trading commodity, resulting in more administrative liability and not yet fully protecting investors. In contrast, Japan, through its Financial Services Agency (FSA), has designated crypto as a legal means of payment with a stronger protection system. This research confirms that the role of government and exchanges is the most important factor in achieving effective legal protection in the crypto asset sector.